Synergistic effects of biochar and probiotic fermentation agent on soil aggregate stability, carbon sequestration, and heavy metal(loid)s passivation in paddy fields - Keqi Zhao; Xue Yu; Xifeng Qin; Ruijie Li; Lin Luo; Xiaomei Yang; Liuqin He; Anwei Chen; Jiachao Zhang; Hongli Huang; Xichen Zhao (Agriculture, Ecosystems & Environment, 2026)

Interfacial effects of a ternary heterostructure on 1 T/2H MoS2 for Pt/C-comparable alkaline hydrogen evolution at industrially relevant high current densities - Nan Zhang; Menglin Gao; Wenru Cheng; Zhaocun Song; Xichen Yang (Journal of Environmental Chemical Engineering, 2026)

Phenological divergence in the rice stem borer correlates with rice domestication - Meng Wang; Xiurou Mo; Xinting Qiu; Shiqing Yuan; Yue Liu; Xichen Xiao; Meijuan Yang; Yongmo Wang (Evolutionary Ecology, 2026)

Spin-state modulation via cu incorporation in NiFe-LDHs: A novel strategy for surface-enhanced Raman scattering biosensing - Chaoqin He; Jingzhi Zhou; Xichen Shi; Ruo Yuan; Ying Zhuo; Xia Yang (Chemical Engineering Journal, 2026)

Substitution-degree-engineered acetylated curdlan Janus dressing: Unidirectional self-pumping for efficient wound exudate management and accelerated healing - Shaojing Yang; Shixiong Yang; Yixuan Cai; Jia Zou; Xichen Qiao; Rui Wang; Huajun Wang; Xiaofei Zheng; Hairong Xiong; Zongbao Zhou (Carbohydrate Polymers, 2026)

Chrysanthemum classification method via multi-stream deep color space feature fusion - Jian Jiang; Xichen Yang; Hui Yan; Jia Liu; Yifan Chen; Zhongyuan Mao; Tianshu Wang (Computers and Electronics in Agriculture, 2026)

Dynamic boronic ester bonded shape memory elastomer with high mechanical strength and energy dissipation properties for vibration and impact protection - Qili Yu; Guangyu Sun; Xichen Yang; Qunfu Fan; Yujie Chen; Hezhou Liu (Chemical Engineering Journal, 2025)

SERS biosensor based on the Cas13a assisted entropy-driven system and lychee-like Fe–TiO2 with excellent exciton capture and separation - Jingzhi Zhou; Xichen Shi; Chaoqin He; Xiuwen Zheng; Ruo Yuan; Xia Yang (Analytica Chimica Acta, 2025)

Dynamic Characteristic (Axial Impedances) of a Novel Sandwich Flexible Insert with Fluid - Leipeng Song; Lulu Chang; Feng Li; Xinjian Xiang; Zhiyong Yin; Xichen Hou; Yongping Zheng; Xiaozhou Xu; Yang Li; Zhihua Huang (Journal of Marine Science and Engineering, 2025)
Piping systems can be analogized to the “vascular systems” of vessels, but their transmission characteristics often result in loud noises and large vibrations. The integration of flexible inserts within these piping systems has been shown to isolate and/or mitigate such vibrations and noise. In this work, a novel sandwich flexible insert (NSFI) was presented specifically to reduce the vibrations and noise associated with piping systems on vessels. In contrast to conventional flexible inserts, the NSFI features a distinctive three-layer configuration, comprising elastic inner and outer layers, along with a honeycomb core exhibiting a zero Poisson’s ratio. The dynamic characteristics, specifically axial impedance, of the fluid-filled NSFI are examined utilizing a fluid–structure interaction (FSI) four-equation model. The validity of the theoretical predictions is corroborated through finite element analysis, experimental results, and comparisons with existing literature. Furthermore, the study provides a comprehensive evaluation of the effects of geometric and structural parameters on the dynamic characteristics of the NSFI. It is worth noting that axial impedance is significantly affected by these parameters, which suggests that the dynamic characteristics of the NSFI can be customized by parameter adjustments.

Remote effect of tropical South Atlantic variability on the Pacific–Japan pattern - Wenwen Yang; Xichen Li; Lin Wang; Yurong Hou; Yonghao Wang; Yujie Miao; Weihan Ma (Climate Dynamics, 2025)

Synergistic inactivation effect of ultrasound and nano-emulsified basil essential oil on the metabolic responses of Salmonella on sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Lijing Ke; Chao Shi; Hongshun Yang; Lingchi Deng; Zejia Lin; Lin Chen (International Journal of Food Microbiology, 2025)

An RPA-CRISPR/Cas12a-assisted method for nucleic acid detection of Haemonchus contortus in sheep - Yutong Cao; Qiankun Yang; Yanbing Guo; Xiaocen Wang; Xin Li; Nan Zhang; Wenxue Lu; Jianhua Li; Xichen Zhang; Lili Cao; Pengtao Gong (Veterinary Parasitology, 2025)

Photo-induced multiple charge transfer resonance of Ce-MOF for SERS detection of nucleic acid - Chaoqin He; Lingling Jiang; Xichen Shi; Ying Zhuo; Ruo Yuan; Xia Yang (Analytica Chimica Acta, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Optimizing the management of aerobic composting for antibiotic resistance genes elimination: A review of future strategy for livestock manure resource utilization - Keqi Zhao; Xiaowei Yin; Nanyi Wang; Nianqiao Chen; Youming Jiang; Linyan Deng; Wenbo Xiao; Kun Zhou; Yong He; Xichen Zhao; Yuan Yang; Jiachao Zhang; et al. (Journal of Environmental Management, 2024)

Exploring the potential of ultrasound combined with sucrose treatments for germination and growth of sunflower sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Hongshun Yang; Zejia Lin; Lin Chen (Food Bioscience, 2024)

Nanopaper-based sensors with ultrahigh and stable conductance for wearable sensors and heaters - Xichen Yu; Zhuqun Shi; Chuanxi Xiong; Quanling Yang (Chemical Engineering Journal, 2024)

Mo-doped Co LDHs as Raman enhanced substrate for detection of roxarsine - Xichen Shi; Chaoqin He; Lingling Jiang; Huan Liang; Xinli Zhang; Ruo Yuan; Xia Yang (Analytica Chimica Acta, 2024)

Axial behavior of slugging flow in a gas–solid CFB riser using distributed ECVT with 64 electrodes - Aofang Guo; Daoye Yang; Xichen Gu; Shuxian Zhang; Mengtao Zhang (Chemical Engineering Journal, 2024)

Pyrolysis and combustion characteristics of typical sealing materials for exterior building windows - Yaqing Li; Jie Yang; S. Zeinali Heris; Yutao Zhang; Xichen Zhang; Jiannan Chen (Fuel, 2024)

Bioinspired anisotropic PEEK for solvent sensing and programmable actuations - Wenhui Chen; Xiaolong Zhang; Xichen Yang; Baisong Yang; Daobing Chen; Yifeng Lei; Sheng Liu; Longjian Xue (Chemical Engineering Journal, 2023)

Rice yield benefits from historical climate warming to be negated by extreme heat in Northeast China - Xin Dong; Tianyi Zhang; Xiaoguang Yang; Tao Li; Xichen Li (International Journal of Biometeorology, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Specific Relationship between the Surface Air Temperature and the Area of the Terra Nova Bay Polynya, Antarctica - Yifan Ding; Xiao Cheng; Xichen Li; Mohammed Shokr; Jiawei Yuan; Qinghua Yang; Fengming Hui (Advances in Atmospheric Sciences, 2020)

Complete genome sequence and evolution analysis of Eimeria stiedai RNA virus 1, a novel member of the family Totiviridae - Caiyan Xin; Bin Wu; Jianhua Li; Pengtao Gong; Ju Yang; He Li; Xuepeng Cai; Xichen Zhang (Archives of Virology, 2016)

Cytochrome P450 2A13 is an efficient enzyme in metabolic activation of aflatoxin G1 in human bronchial epithelial cells - Zhan Zhang; Xuejiao Yang; Yun Wang; Xichen Wang; Huiyuan Lu; Xiaoming Zhang; Xue Xiao; Shushu Li; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

Protective effect of gossypol on lipopolysaccharide-induced acute lung injury in mice - Zhicheng Liu; Zhengtao Yang; Yunhe Fu; Fenyang Li; Dejie Liang; Ershun Zhou; Xiaojing Song; Wen Zhang; Xichen Zhang; Yongguo Cao; Naisheng Zhang (Inflammation Research, 2013)

Salidroside attenuates inflammatory responses by suppressing nuclear factor-κB and mitogen activated protein kinases activation in lipopolysaccharide-induced mastitis in mice - Depeng Li; Yunhe Fu; Wen Zhang; Gaoli Su; Bo Liu; Mengyao Guo; Fengyang Li; Dejie Liang; Zhicheng Liu; Xichen Zhang; Yongguo Cao; Naisheng Zhang; et al. (Inflammation Research, 2013)